PENILAIAN RISIKO KEAMANAN BENDUNGAN DI JAWA TIMUR - Maria Asunta Hana Pramudawati; Mahdi Ibrahim Tanjung; Ranisa Ghafara (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Dam risk assessment is basically a additional to a standard-based approach, which is a conservative approach to dam engineering. For existing and new dams, dam risk assessment aims to determine whether existing hazard risks can be tolerated, and if hazard risks cannot be tolerated, actions to reduce risk are planned. Risk assessments for existing dams can also be used as a basis for determining priorities in carrying out the required repair or rehabilitation work. This paper discusses the dam risk assessment at Sengguruh Dam, Sutami Dam, Lahor Dam, Wlingi Dam, Bening Dam, Wonorejo Dam and Selorejo Dam. The methods used in risk assessment include the preparation of risk assessments, risk analysis, risk evaluation, risk reduction and management. These seven dams are managed by one manager, namely PJT I and are considered to be representative of this method that can be used to determine the priority value of dam handling. Based on the results of the assessment, the 7 dams fulfill the risk criteria. The next action that can be taken for these dams is to monitor the dam's behavior on a regular basis and in the aftermath of the earthquake, renew and socialize the RTD.